Time‐resolved ion imaging at free‐electron lasers using TimepixCam. (20th February 2018) - Fisher-Levine, Merlin; Boll, Rebecca; Ziaee, Farzaneh; Bomme, Cédric; Erk, Benjamin; Rompotis, Dimitrios; Marchenko, Tatiana; Nomerotski, Andrei; Rolles, Daniel
Abstract : The application of a novel fast optical‐imaging camera, TimepixCam, to molecular photoionization experiments using the velocity‐map imaging technique at a free‐electron laser is described. TimepixCam is a 256 × 256 pixel CMOS camera that is able to detect and time‐stamp ion hits with 20 ns timing resolution, making it possible to record ion momentum images for all fragment ions simultaneously, thus avoiding the need to gate the detector on a single fragment. Abstract : The application of a novel fast optical‐imaging camera, TimepixCam, to molecular photoionization experiments using the velocity‐map imaging technique at a free‐electron laser is described. TimepixCam is a 256 × 256 pixel CMOS camera that is able to detect and time‐stamp ion hits with 20 ns timing resolution, thus making it possible to record ion momentum images for all fragment ions simultaneously and avoiding the need to gate the detector on a single fragment. This allows the recording of significantly more data within a given amount of beam time and is particularly useful for pump–probe experiments, where drifts, for example, in the timing and pulse energy of the free‐electron laser, severely limit the comparability of pump–probe scans for different fragments taken consecutively. In principle, this also allows ion–ion covariance or coincidence techniques to be applied to determine angular correlations between fragments.